STUDI SEROEPIDEMIOLOGIS CHLAMYDIA PNEUMONIAE DAN BEBERAPA MIKROORGANISME YANG DIDUGA MENYEBABKAN INFARK MIOKARD AKUT - Murwani, Sri; Ali, Mulyohadi; Muliartha, Ketut; Purwanto, Purwanto; Susilawati, Ida; Nur Aini, Dinda; Yuni, Yuni (Lembaga Penelitian Universitas YARSI, 2007)
Acute myocardial infarction (AMI) is still a major health problem. Approximately 20% of death in the world was caused by atherosclerotic diseases like stroke, myocardial infarct. Recent studies explain the role of infection in the pathogenicity of AMI. The purpose of this study was to examine seroepidemiological study of Chlamydia pneumoniae infection related to AMI and its occurrence as pathogen burden-infection with other microorganisms. Subjects for this study were patients diagnosed clinically and laboratorically as AMI, from RSUD Saiful Anwar and RS. Lavalette,Malang. Blood samples were collected from each subject and serum was analyzed for IgG antibodies against C. pneumoniae, CMV, H. pylori and S. mutans. Clinical status was analyzed to find IMA conventional risk factors, such as smoking, hypertension, hypercholesterolemia, and diabetes mellitus. The result showed that the average age of these patients were 55 years and men were more common than women. All of these patients were infected by microorganism. Patients with infection and conventional risk factors were 51,9%, infection without conventional risk factors was 48,2%, and conventional risk factors for IMA without infection was 51, 85%. The most common conventional risk factor was smoking (37, 0%). Infection by S. mutans was detected in all patients (100%), C. pneumoniae 92,6%, CMV 92,6%, H. pylori 77,8%; however multiple infections were observed in most of the patients. It was concluded that microorganisms played rolesin the pathogenicity of IMA. It was suggested that the development of IMA might be contributed by single infection as well as multiple infections. However, multiple infections tend to be observed in most of the patients.